Ultrafast optical response of a high-reflectivity GaAs∕AlAs Bragg mirror - Hastings, Sara R.; de Dood, Michiel J. A.; Kim, Hyochul; Marshall, William; Eisenberg, Hagai S.; Bouwmeester, Dirk (Appl. Phys. Lett., 2005)
The ultrafast response of a high-reflectivity GaAs∕AlAs Bragg mirror to optical pumping is investigated for all-optical switching applications. Both Kerr and free carrier nonlinearities are induced with 100 fs, 780 nm pulses with a fluence of 0.64 and 0.8kJ∕m2. The absolute transmission of the mirror at 931 nm increases by a factor of 27 from 0.0024% to 0.065% on a picosecond time scale. These results demonstrate the potential for a high-reflectivity ultrafast switchable mirror for quantum optics and optical communication applications. A design is proposed for a structure to be pumped below the band gaps of the semiconductor mirror materials. Theoretical calculations on this structure show switching ratios up to 2200 corresponding to switching from 0.017% to 37.4% transmission.